ANALISIS PENGUKURAN KINERJA BERBASIS BALANCED SCORECARD PADA KANTOR PELAYANAN PAJAK PRATAMA SINGOSARI - Sari, Nur Ita (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Performance measurement is a necessary thing in an organization in order to improve the quality of products and services that are owned as well as public sector organizations such as the STO Singosari. This study used descriptive qualitative approach. The analytical method used to measure four balanced scorecard perspectives is financial perspective, customer, internal business processes and growth and development. Results from the study indicate that the financial perspective is measured from tax revenues provide good results, although not fully realized. The realization of tax revenue on STO Singosari decreased from 2014 to 2015 from 93.18% to 92.35%. From a customer perspective can be concluded that the performance of the service provided is good. Internal business processes perspective also showed that the STO Singosari is able to provide service innovations so it make the process faster process. And for the perspective of growth and development has shown good results for most employees already qualified and available information network system has supported the company's performance.